Physical-Mechanical Properties and Bonding Mechanism of Corn Stalks Particleboard with Citric Acid Adhesive - Kurnia Wiji Prasetiyo; Linda Oktaviani; Lilik Astari; Firda Aulya Syamani; Subyakto Subyakto; Suminar S Achmadi (Masyarakat Peneliti Kayu Indonesia, 2018)
As a natural fiber and agricultural by-product, corn stalks (Zea mays saccharata) is considered as an alternative raw material to produce particleboard. Corn stalks is a good source of lignocelluloses, renewable and low cost. This research was aimed to investigate the characteristics of corn stalk particleboard with citric acid as adhesive. This study also evaluated bonding mechanism particle with citric acid and the bonds between celluloses derived corn stalk with citric acid. The boards were manufactured under the hot pressing temperature 200 oC for 10 min. The citric acid concentration was varied in 0, 15, 20 and 25 wt%. The board size and target density were (25 x 25 x 0.9) mm3 and 0.8 g.cm‑3. Results showed that the physical properties of particleboards improved with increasing citric acid concentration up to 20 wt%. At the optimum citric acid content of 20 wt% could provide particleboards with the modulus of rupture, modulus of elasticity and internal bonding satisfied the requirement of the 13 type of the JIS A 5908 (2003) standard. Infrared (IR) spectral analysis from board which manufactured from isolated cellulose was mixed citric acid and pressed on temperature 200 oC showed the presence of ester linkages that the carboxyl and hydroxyl groups of citric acid had reacted with the hydroxyl groups of corn stalk cellulose.